ACCOUNTING FOR FARMERS' ATTITUDE TOWARDS RISK IN THE APPLICATION OF IMPROVED FARM TECHNOLOGIES: THE CASE OF INORGANIC FERTILIZER USE IN OYO NORTH AREA OF OYO STATE, NIGERIA - OSOTIMEHIN , K.O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The knowledge of farmers' choice behaviour is important in terms of both micro and macro strategies for agricultural development. This is particularly important if their interests are to be taken into consideration when designing new technologies for their mass acceptance. This study measures farmers' attitudes toward risk in the application of inorganic fertilizer, through the method of observed economic behaviour with respect to input demand and output supply. The measured coefficients were correlated with the socio-economic characteristics of the respondents. Results indicate that institutional factors have significant influence in explaining the exhibited risk behaviours. However, the adjusted R2 was found to be 0.37, suggesting that some other important variables outside socio-economic characteristics might also be important in explaining farmers' risk attitudes. Recommendations were made toward the use of the identified factors in the analysis to enhance wider application of inorganic fertilizer.